ANALISIS FIKIH IMAM SYAFI’I TERHADAP PERALIHAN RISIKO JUAL BELI DALAM PASAL 1460 KUH PERDATA - Diki Kurniawan (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research aims to determine the transition of trade risk, also as the object of this research and to know the opinion of imam Shafi’i to the transition of trade risk, This research is a normative study by using fiqh Imam Shafi’i and code of civil law. with a conceptual approach and a statue approach, this approach is more emphasis on the discussion that analyzes the article 1460 Civil Code about the trade and the opinion of imam Shafi’i. the technique of collecting legal materials in this research is by literature study, literary studies include the study of legal materials comprising of primary, secondary, and tertiary legal materials, the result of this research is the buyer's loading in Civil Code that is risk of goods sold according to pile. whereas according to imam Shafi’i goods pile is the responsibility of the seller with the terms of the goods mentioned.